2015
DOI: 10.3892/or.2015.4084
|View full text |Cite
|
Sign up to set email alerts
|

Evodiamine inhibits the proliferation of human osteosarcoma cells by blocking PI3K/Akt signaling

Abstract: Abstract. Osteosarcoma (OS) is the most common non-hematologic primary malignancy of bone, and multiple chemotherapeutic agents have been applied in the treatment of OS for over 40 years. Nevertheless, due to the poor prognosis of OS, it is essential to develop a novel treatment strategy. Evodiamine (EVO), a quinolone alkaloid extracted from the fruit of Evodia rutaecarpa, has been demonstrated to inhibit tumor cell proliferation. Thus, the main aim of the present study was to investigate the anti-proliferativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…GO terms related to translation (e.g., cytoplasmic translation) were also enriched in OS genes. In line with previous studies, several pathways, such as mTOR signaling pathway (ranked 5th) (29,30), Hippo signaling pathway (ranked 9th) (31), PI3K-Akt signaling pathway (ranked 10th) (30,32), MAPK signaling pathway (ranked 11th) (33), Wnt signaling pathway (ranked 22nd) (34,35), p53 signaling pathway (ranked 24th) (36–38), and TGF-β signaling pathway (ranked 27th) (38,39), were enriched in OS genes. In addition, several cancer-related pathways were identified, such as Pathways in cancer, Proteoglycans in cancer, central carbon metabolism in cancer, and transcriptional misregulation in cancer.…”
Section: Resultssupporting
confidence: 89%
“…GO terms related to translation (e.g., cytoplasmic translation) were also enriched in OS genes. In line with previous studies, several pathways, such as mTOR signaling pathway (ranked 5th) (29,30), Hippo signaling pathway (ranked 9th) (31), PI3K-Akt signaling pathway (ranked 10th) (30,32), MAPK signaling pathway (ranked 11th) (33), Wnt signaling pathway (ranked 22nd) (34,35), p53 signaling pathway (ranked 24th) (36–38), and TGF-β signaling pathway (ranked 27th) (38,39), were enriched in OS genes. In addition, several cancer-related pathways were identified, such as Pathways in cancer, Proteoglycans in cancer, central carbon metabolism in cancer, and transcriptional misregulation in cancer.…”
Section: Resultssupporting
confidence: 89%
“…Recent evidence has also confirmed that the protein expression of PTEN could be suppressed by microRNAs and PTEN is confirmed to be target for miR-213031. Research also found that PTEN could reduce the phosphorylation of AKT protein32, which was involved in hypertrophic scar formation33. Moreover, the expression of PTEN could be effectively inhibited by TGF-β34.…”
Section: Discussionmentioning
confidence: 90%
“…143B cells were seeded in T25 flasks and treated with the indicated infection rates of AdBMP9 for 48 h. Total RNA was extracted using the TRIzol reagent (Invitrogen, Carlsbad, CA, USA) and used to obtain cDNA templates by reverse transcription (RT). Then, the cDNAs were used as templates for determining the expression of target genes by semi-quantitative PCR (sqPCR), as described (36). The primers for each gene were as follows: GAPDH, F:…”
Section: Reverse Transcription and Polymerase Chain Reaction Analysismentioning
confidence: 99%
“…The detailed method was previously described (36). In brief, subconfluent 143B cells were plated in 6-well plates and treated with the indicated concentrations of ATRA and/or AdBMP9 and/or SB203580.…”
Section: Reverse Transcription and Polymerase Chain Reaction Analysismentioning
confidence: 99%